2002
DOI: 10.1161/01.cir.0000022665.18619.83
|View full text |Cite
|
Sign up to set email alerts
|

Use of Irbesartan to Maintain Sinus Rhythm in Patients With Long-Lasting Persistent Atrial Fibrillation

Abstract: Background-Data from studies of angiotensin-converting enzyme inhibitors provide evidence that the renin-angiotensin-aldosterone system plays a role as a mediator of atrial remodeling in atrial fibrillation. The present study has evaluated the effect of treatment with the angiotensin I type 1 receptor blocker irbesartan on maintaining sinus rhythm after conversion from persistent atrial fibrillation. Methods and Results-To be included in the present study, patients must have had an episode of persistent atrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
0
12

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 620 publications
(157 citation statements)
references
References 26 publications
4
141
0
12
Order By: Relevance
“…It has revealed in the CHARM program 23 that treatment with the angiotensin receptor blocker candesartan, reduced the incidence of AF in a large, broadly-based, population of patients with symptomatic chronic heart failure, which provided the opportunity to prospectively determine the effect of candesartan on the incidence of new AF in this CHF population. Madrid et al 24 found that patients treated with amiodarone plus irbesartan had a lower rate of recurrence of atrial fibrillation than did with amiodarone alone. Therefore, it is interesting to investigate whether ARBs which contain PPARγ-activating potential have superior effects in reducing the development of AF in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has revealed in the CHARM program 23 that treatment with the angiotensin receptor blocker candesartan, reduced the incidence of AF in a large, broadly-based, population of patients with symptomatic chronic heart failure, which provided the opportunity to prospectively determine the effect of candesartan on the incidence of new AF in this CHF population. Madrid et al 24 found that patients treated with amiodarone plus irbesartan had a lower rate of recurrence of atrial fibrillation than did with amiodarone alone. Therefore, it is interesting to investigate whether ARBs which contain PPARγ-activating potential have superior effects in reducing the development of AF in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…66 Atrial antifibrillatory effects Several recent studies have demonstrated that ARBs either decrease the recurrence of pre-existing atrial fibrillation (AF) after conversion to sinus rhythm, or prevent the new onset of AF. 68,69 Administration of irbesartan 150-300 mg/day in combination with amiodarone 400 mg/day was administered to 79 patients after conversion of chronic AF to sinus rhythm and compared with 75 similar patients treated with amiodarone 400 mg/day. After a median observation time of 254 days, 79.52% of patients on irbesartan plus amiodarone and 55.91% of patients on amiodarone alone remained in sinus rhythm, 69 which was statistically significant (P ¼ 0.007).…”
Section: Aii-mediated Effects Of Arbsmentioning
confidence: 99%
“…27 More recently, the ARB irbesartan, given in combination with amiodarone, following cardioversion for persistent AF, significantly reduced the recurrence rate of AF compared with amiodarone alone. 28 A reduction in the incidence of new onset AF with losartan was also demonstrated in the LIFE study, suggesting that the RAAS may have an intrinsic role in the generation of this arrhythmia, perhaps via its role in left atrial remodelling or electrophysiological effects. Indeed, if angiotensin II blockade (directly by receptor antagonism, or indirectly through ACE inhibition) does reduce the frequency of new onset AF then this too could be another mechanism by which stroke risk is reduced.…”
Section: New Onset Afmentioning
confidence: 72%